2004
DOI: 10.1080/03079450400003601
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of outbreaks of highly pathogenic H5N1 avian influenza in waterfowl and wild birds in Hong Kong in late 2002

Abstract: Outbreaks of highly pathogenic H5N1 avian influenza have occurred in Hong Kong in chickens and other gallinaceous poultry in 1997, 2001, twice in 2002 and 2003. High mortality rates were seen in gallinaceous birds but not in domestic or wild waterfowl or other wild birds until late 2002 when highly pathogenic H5N1 avian influenza occurred in waterfowl (geese, ducks and swans), captive Greater Flamingo (Phoenicopterus ruber) and other wild birds (Little Egret Egretta garzetta) at two waterfowl parks and from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
318
1
7

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(335 citation statements)
references
References 18 publications
9
318
1
7
Order By: Relevance
“…While most affected wild bird species inhabit wetlands or aquatic habitats (Olsen et al, 2006;Stallknecht and Brown, 2007), HPAI H5N1 has been isolated from wildcaught passerines including live Eurasian Tree Sparrows in China (Kou et al, 2005) and a dead one in Hong Kong (Ellis et al, 2004). A recent HPAI H5N1 isolate from a tree sparrow linked to limited transmission among humans in China (Liu et al, 2010) and a relatively high prevalence of AIVs in passerines in the USA (Fuller et al, 2010) also motivate a closer look at the occurrence of AIVs in wild-caught passerines.…”
mentioning
confidence: 99%
“…While most affected wild bird species inhabit wetlands or aquatic habitats (Olsen et al, 2006;Stallknecht and Brown, 2007), HPAI H5N1 has been isolated from wildcaught passerines including live Eurasian Tree Sparrows in China (Kou et al, 2005) and a dead one in Hong Kong (Ellis et al, 2004). A recent HPAI H5N1 isolate from a tree sparrow linked to limited transmission among humans in China (Liu et al, 2010) and a relatively high prevalence of AIVs in passerines in the USA (Fuller et al, 2010) also motivate a closer look at the occurrence of AIVs in wild-caught passerines.…”
mentioning
confidence: 99%
“…9 Experimentally, an early H5N1 HPAI isolate (A/chicken/Hong Kong/220/97 [H5N1]) was only capable of low-level replication in house sparrows (Passer domesticus), a species closely related to tree sparrows, and caused mild clinical signs but no mortality. 22 An infectivity trial performed with 4 different 2005-2006 H5N1 HPAI viruses, however, indicated that more recent isolates were highly virulent for house sparrows causing 66-100% mortality in intranasally inoculated birds.…”
Section: Introductionmentioning
confidence: 99%
“…13,27 Similarly, mortality in columbids associated with natural and confirmed H5N1 HPAI virus infections have been reported but generally are rare events involving a few individual birds. 9 Pigeons and sparrows likely represent 2 extremes of susceptibility to H5N1 HPAI virus among wild terrestrial birds commonly found around poultry environments. However, discrepancies and knowledge gaps in the existing body of data on these 2 species make it difficult to understand the potential role that either species may play in the epidemiology of H5N1 HPAI virus.…”
Section: Introductionmentioning
confidence: 99%
“…Before the detection of highly pathogenic avian influenza (HPAI) H5N1 virus in wild birds during 2002 (Ellis et al, 2004), isolations of HPAI from free-living wild bird populations were restricted to a single event in 1961, when an HPAI virus (A/tern/South Africa/61 [H5N3]) caused the deaths of approximately 1,300 Common Terns (Sterna hirundo) in South Africa (Becker, 1966). The South African event provided the first evidence of a wild bird reservoir for avian influenza viruses (AIV) and resulted in significant wild bird surveillance during the next 45 yr.…”
Section: Introductionmentioning
confidence: 99%